Alterations in the Levels of Circulating and Endothelial Progenitor Cells Levels in Young Adults with Type 1 Diabetes: A 2-Year Follow-Up from the Observational METRO Study - Longo M (Dove Medical Press, 2020)
Miriam Longo,1,2 Lorenzo Scappaticcio,1 Giuseppe Bellastella,1,2 Vlenia Pernice,1 Paolo Cirillo,1 Antonietta Maio,1 Filomena Castaldo,1,2 Dario Giugliano,1,2 Katherine Esposito,1,3 Maria Ida Maiorino1,2 On Behalf of the METRO Study Group1Department of Advanced Medical and Surgical Sciences, University of Campania “Luigi Vanvitelli”, Naples 80138, Italy; 2Unit of Endocrinology and Metabolic Diseases, University of Campania “Luigi Vanvitelli”, Naples 80138, Italy; 3Unit of Diabetes, University of Campania “Luigi Vanvitelli”, Naples 80138, ItalyCorrespondence: Maria Ida MaiorinoUnit of Endocrinology and Metabolic Diseases, Department of Advanced Medical and Surgical Sciences, University of Campania “Luigi Vanvitelli”, Piazza Miraglia 2, Naples 80138, ItalyTel +39 0815665289Fax +39 0815665032Email mariaida.maiorino@unicampania.itPurpose: Type 1 diabetes is associated with high risk of cardiovascular disease (CVD). Reduced levels of circulating progenitor cells (CPCs) and endothelial progenitor cells (EPCs) have been indicated as a risk factor for adverse cardiovascular outcomes and death in people at high cardiovascular risk. The aim of the present study was to evaluate the change in CPCs and EPCs levels in a population of young type 1 diabetic patients treated with intensive insulin regimen over a period of 2 years.Patients and Methods: A total of 204 type 1 diabetic patients, of whom 84 treated with insulin pump (CSII) and 120 with multiple daily insulin injections (MDI), completed a 2-year follow-up. Clinical measurements, including the indices of glycemic control and glucose variability, were collected at baseline and after 2 years. Both CPC and EPC cell count were assessed by flow cytometry.Results: Mean age of participants was 24.5 years and mean diabetes duration was 13.6 years. After 2 years, we found a significant reduction of HbA1c (− 0.3% versus baseline, P < 0.001), associated with decrease in mean amplitude of glucose excursion (MAGE) (− 0.5 mmol/L versus baseline, P< 0.001), continuous overall net glycemic action (CONGA) (− 0.2 mmol/L versus baseline, P=0.006), and blood glucose standard deviation (BGSD) (− 0.2 mmol/L versus baseline, P< 0.001). The number of all EPCs phenotypes, but not CPC cell count, significantly raised up in the entire population, with higher increase in CSII group. MAGE resulted as an independent predictor for increased levels of both CD34+ (P = 0.020) and CD34+KDR+ (P = 0.004) cell count in the whole population.Conclusion: Over a 2-year follow-up, young type 1 diabetic patients showed an increase in circulating EPCs levels, which was higher in patients with CSII. Glucose variability resulted as an independent predictor of the raised levels of EPCs in this selected population.Keywords: endothelial progenitor cells, circulating progenitor cells, glucose variability, type 1 diabetes, CSII, MDI